2022
DOI: 10.3390/molecules27196572
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Positive and Negative Regulatory Effects of Rhein on the Kidney: A Review of Its Molecular Targets

Abstract: Currently, both acute kidney injury (AKI) and chronic kidney disease (CKD) are considered to be the leading public health problems with gradually increasing incidence rates around the world. Rhein is a monomeric component of anthraquinone isolated from rhubarb, a traditional Chinese medicine. It has anti-inflammation, anti-oxidation, anti-apoptosis, anti-bacterial and other pharmacological activities, as well as a renal protective effects. Rhein exerts its nephroprotective effects mainly through decreasing hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 134 publications
0
6
0
Order By: Relevance
“…Studies ( Ma et al, 2018 ) have found that emodin can inhibit the expression of transforming growth factor β1, block the TGF-β1/Smad signaling pathway, and inhibit the transdifferentiation of human renal tubular epithelial cells (HK-2), thereby reducing epithelial-myofibroblast transdifferentiation (TEMT). Rhein and its derivatives, analogs, and compound preparations protect against various kidney diseases, particularly diabetic nephropathy (DN) and drug-induced AKI ( Zhu et al, 2022 ). In the research of Luo Yan et al, Rhein was found to restrain the SHH-Gli1-Snail signal pathway, extenuating renal fibrosis in rhein-treated UUO rats ( Luo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies ( Ma et al, 2018 ) have found that emodin can inhibit the expression of transforming growth factor β1, block the TGF-β1/Smad signaling pathway, and inhibit the transdifferentiation of human renal tubular epithelial cells (HK-2), thereby reducing epithelial-myofibroblast transdifferentiation (TEMT). Rhein and its derivatives, analogs, and compound preparations protect against various kidney diseases, particularly diabetic nephropathy (DN) and drug-induced AKI ( Zhu et al, 2022 ). In the research of Luo Yan et al, Rhein was found to restrain the SHH-Gli1-Snail signal pathway, extenuating renal fibrosis in rhein-treated UUO rats ( Luo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, anthraquinones could reduce toxicity and enhance protective effects by the compatibility of traditional Chinese medicine. 62 This study suggested that BT, ST, and AT could effectively decrease the anthraquinone content of CWEs by 35.9, 27.3, and 93.8%, respectively. Therefore, the treatment method can be adjusted according to the final anthraquinone content, which could exert the biological activity of the anthraquinones and decrease negative effects.…”
Section: Discussionmentioning
confidence: 72%
“…Zhu et al clarified that rhein regulated the function of the kidney in both a positive and negative way and further proposed the methods of using rhein reasonably and safely. 62 Qu et al evaluated the acute and subchronic toxicity of anthraquinones and found that the lowest observed adverse effect level was 5.44 mg/kg body weight and that there were no observed adverse effects at 1.36 mg/kg body weight. 63 These results demonstrated that anthraquinones played a dual role in bioactivities, and so the use of anthraquinones should be treated cautiously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, rhein has been widely used in the treatment of sepsis and other critical and critical fields [5]. Studies have found that [6,7], rhein can down regulate proinflammatory cytokines and signal transduction through NF-KB and other signal pathways. Previous experiments have established that Rhein is effective in inhibiting fibronectin and the excessive inhibition of TGF-H, thereby reducing the accumulation of extracellular matrix, protecting renal function, and improving renal histological changes, which suggests that rhein may also play a protective role in renal injury.…”
Section: Introductionmentioning
confidence: 99%